Midazolam microdosing applied in early clinical development for drug-drug interaction assessment - Wiebe, Sabrina; Huennemeyer, Andreas; Kadus, Werner Uli; Goettel, Markus; Jambrecina, Alen; Schultz, Armin; Vinisko, Richard; Schlieker, Laura; Herich, Lena; Mikus, Gerd (British journal of clinical pharmacology, 2021)
Aims We aimed to incorporate a pharmacologically inactive midazolam microdose into early clinical studies for the assessment of CYP3A drug-drug interaction liability. Methods Three early clinical studies were conducted with substances (Compounds A, B and C) which gave positive CYP3A perpetrator signals in vitro. A 75 μg dose of midazolam was administered alone (baseline CYP3A activity) followed by administration with the highest dose groups tested for each compound on Day 1/3 and Day 14 or Day 17. Midazolam exposure (AUC0-∞, Cmax) during administration with the test substances was compared to baseline data via an analysis of variance on log-transformed data. Partial AUC2-4 ratios were also compared to AUC0-∞ ratios using linear regression on log-transformed data. Results Test compound Cmax values exceeded relevant thresholds for drug-drug interaction liability. Midazolam concentrations were quantifiable over the full profiles for all subjects in all studies. Point estimates of the midazolam AUC0-∞ gMean ratios ranged from 108.3 to 127.1% for Compound A, from 93.3 to 114.5% for Compound B, and from 92.0 to 96.7% for the two highest dose groups of Compound C. Cmax gMean ratios were in the same range. Thus, no relevant drug-drug interactions were evident, based on the results of midazolam microdosing. AUC2-4 ratios from these studies were comparable to the AUC0-∞ ratios. Conclusion Midazolam microdosing incorporated into early clinical studies is a feasible tool for reducing dedicated drug-drug interaction studies, meaning reduced subject burden. Limited sampling could further reduce subject burden, costs and needed resources.